PENGARUH PENGGUNAAN MODEL DISCOVERY LEARNING TERHADAP MINAT BELAJAR PADA MATA PELAJARAN IPAS SISWA SEKOLAH DASAR - Fadilah, Andi; Azizah; Asriani; Herlina (JS (JURNAL SEKOLAH), 2025)
Abstract: This study aims to determine the effect of the Discovery Learning model on the learning interest of Grade IV students at SD Inpres 3 Tondo. This research is a quantitative experimental study conducted on two groups: the experimental group and the control group. The research design used in this study is a quasiexperimental design in the form of a Control Experiment Group Design. The population in this study consists of all Grade IV students at SD Inpres 3 Tondo for the 2024/2025 academic year, totaling 67 students. The sample in this study consists of Class IV A as the control class and Class IV B as the experimental class. The instrument used is a student learning interest questionnaire that has been validated and tested for reliability. Data analysis includes prerequisite tests, namely normality and homogeneity tests, as well as hypothesis testing using the Paired Sample t-Test, analyzed using SPSS for Windows 27. The research results show a significance value (2-tailed) of 0.000 < α 0.05. Since the significance value (2tailed) of 0.000 is less than 0.05, the alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. This means that the use of the Discovery Learning model has an effect on students' learning interest in the IPAS subject. Based on the hypothesis testing results, it can be concluded that the use of the Discovery Learning model influences students' learning interest in the IPAS subject for Grade IV at SD Inpres 3 Tondo. Keyword: Effect, Discovery Learning, Students' Learning Interest, IPAS Subject. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Discovery Learning terhadap minat belajar siswa kelas IV SD Inpres 3 Tondo. Penelitian ini merupakan penelitian kuantitatif eksperimen yang dilakukan pada dua kelompok yaitu kelompok eksperimen dan kelompok kontrol. Desain penelitian yanng digunakan dalam penelitian ini adalah quasi eksperiment dengan bentuk Control experiment group Desain. Populasi dalam penelitian ini adalah keseluruhan siswa kelas IV SD Inpres 3 Tondo Tahun ajaran 2024/2025 berjumlah 67 siswa. Sampel dalam penelitian ini adalah kelas IV A sebagai kelas kontrol dan kelas IV B sebagai kelas eksperimen. Instrumen yang digunakan adalah angket minat belajar siswa yang telah di validitas dan realibilitasnya. Analisis data menggunakan uji persyarat yaitu uji normalitas dan uji homogenitas serta pengujian hipotesis menggunakan Paired Sample t-Test yang dianalisis menggunakan SPSS For Windows 27. Berdasarkan hasil penelitian menunjukkan nilai signifikansi (2tailed) 0,000 < nilai α 0,05. Karena nilai sig (2-tailed) 0,000 < 0,05 maka menerima hipotesis Ha dan menolak hipotesis Ho, artinya penggunaan model pembelajaran Discovery Learning terhadap minat belajar siswa pada mata pelajaran IPAS berpengaruh terhadap minat belajar siswa. Berdasarkan hasil uji coba hipotesis dapat disimpulkan bahwa penggunaan model pembelajaran Discovery Learning berpengaruh terhadap minat belajar siswa pada mata pelajaran IPAS kelas IV SD Inpres 3 Tondo. Kata Kunci: Discovery Learning, Minat Belajar Siswa, Mata Pelajaran IPAS.